Variability in Very Preterm Stillbirth and In-Hospital Mortality Across Europe - Draper, ES (2017)
BACKGROUND AND OBJECTIVE: Stillbirth and in-hospital mortality rates associated with very preterm births (VPT) vary widely across Europe. International comparisons are complicated by a lack of standardized data collection and differences in definitions, registration, and reporting. This study aims to determine what proportion of the variation in stillbirth and in-hospital VPT mortality rates persists after adjusting for population demographics, case-mix, and timing of death. METHODS: Standardized data collection for a geographically defined prospective cohort of VPTs (22+0–31+6 weeks gestation) across 16 regions in Europe. Crude and adjusted stillbirth and in-hospital mortality rates for VPT infants were calculated by time of death by using multinomial logistic regression models. RESULTS: The stillbirth and in-hospital mortality rate for VPTs was 27.7% (range, 19.9%–35.9% by region). Adjusting for maternal and pregnancy characteristics had little impact on the variation. The addition of infant characteristics reduced the variation of mortality rates by approximately one-fifth (4.8% to 3.9%). The SD for deaths <12 hours after birth was reduced by one-quarter, but did not change after risk adjustment for deaths ≥12 hours after birth. CONCLUSIONS: In terms of the regional variation in overall VPT mortality, over four-fifths of the variation could not be accounted for by maternal, pregnancy, and infant characteristics. Investigation of the timing of death showed that these characteristics only accounted for a small proportion of the variation in VPT deaths. These findings suggest that there may be an inequity in the quality of care provision and treatment of VPT infants across Europe.